Multivariate Regression Model for Stature Estimation from Arm Span, Horizontal Fingertip Reach and Foot Length of Igbo Ethnic Group of Nigeria - Oghenemavwe, Loveday Ese; Okoh, Peter Done; Fawehinmi, Hakeem Babatunde; David, Lekpa Kingdom; Irozulike, Faustina Chiamaka; Amadi, Michael Anozie; Oparaocha, Chile A.; Ebieto, Celestine Ebieto (Journal of Complementary and Alternative Medical Research, 2024)
Background: Stature estimation is a major factor in biological profiling for identification of persons Aim: To formulate stature estimation models from arm Span, horizontal fingertip reach, and foot length amongst the Igbo ethnic group of Nigeria. Method:  A total of 399 subjects, (200 females and 199 males) between the ages of 18-40 years were recruited for the study. Standardized anthropometric techniques were used to measure the standing height, arm span, and foot length. Data analysis was carried out using a statistical package for social sciences version 23 to calculate Pearson’s coefficients of correlation and regression equation to formulate stature model variables. Result: The correlation coefficients (R) for height against arm span, horizontal fingertip and foot length were 0.84 for all sampled subjects, 0.79 for male subjects, and 0.90 for female subjects. Multivariate regression models for stature estimation were Stature = 56.62 + AS (0.48 – HFTR (0.006)+FL(1.15) for all subjects; Stature = 62.92+AS(0.42)+HFTR(0.15)+FL(0.88) for male subjects; Stature = 47.73 + AS(0.50) - HFT(0.01) + FL(1.32) for female subjects. Conclusion: This data will be useful to forensic anatomists and anthropologists.